2022
DOI: 10.1002/admi.202200796
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Doped Barium Niobate Based Electrocatalysts for Effective Electrochemical Coupling of Methane to Ethylene

Abstract: Methane conversion into value‐added products such as olefins and aromatics is gaining increased attention in the wake of new natural gas reserve discoveries. Electrochemical oxidative coupling of methane (E‐OCM) provides better product selectivity as the product distribution can be controlled by applied potential as well as the oxide ion flux. Here a new catalyst based on Mg and Fe codoped barium niobate perovskites is reported. The prepared perovskites show excellent chemical stability in CH4‐rich environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Thus, here we explored the use of a perovskite material previously demonstrated to be stable for CO 2 gas sensing applications, BaMg 0.33 Nb 0.67-x Fe x O 3-δ (BMNF) (1). When using BMNF as an anode for E-OCM, we found that this material is both capable of converting methane into ethylene products (at cell voltages >0V versus air) and withstanding high temperature holds at temperatures up to 900 °C for over 100 hours without coking or structural collapse (2). Therefore, this article aims to explore how this class of perovskites at lower doping levels maintains stability in methane environments, via temperature programmed reaction (TPR) measurements, as well as further property modifications via doping or by decorating the parent barium magnesium niobate with Fe nanoparticles.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Thus, here we explored the use of a perovskite material previously demonstrated to be stable for CO 2 gas sensing applications, BaMg 0.33 Nb 0.67-x Fe x O 3-δ (BMNF) (1). When using BMNF as an anode for E-OCM, we found that this material is both capable of converting methane into ethylene products (at cell voltages >0V versus air) and withstanding high temperature holds at temperatures up to 900 °C for over 100 hours without coking or structural collapse (2). Therefore, this article aims to explore how this class of perovskites at lower doping levels maintains stability in methane environments, via temperature programmed reaction (TPR) measurements, as well as further property modifications via doping or by decorating the parent barium magnesium niobate with Fe nanoparticles.…”
Section: Introductionmentioning
confidence: 79%
“…Figure 2a features BMN, BaMg 0.33 Nb 0.67 O 3-δ without any Fe, to test the reactivity of the perovskite. Previously, it was found that the conductivity of these BMNF materials was greatly enhanced by the addition of Fe (2). The BMN material has a conductivity <<1 mS/cm, making it effectively an insulator at these reaction conditions.…”
Section: Temperature Programmed Reaction and Stem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported Mg and Fe codoped barium niobates for EOCM application where it showed good methane activation and chemical stability properties under these conditions (12). However, their electrical conductivity at 900 C was only about 17 mScm -1 that restricted the overall achievable current densities.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Hence, significant effort is also being undertaken to sense methane leaks efficiently or to convert it into higher hydrocarbons to reduce fugitive emissions and flaring. 21,22 The other carrier, ammonia can be harmful to human and animal health if inhaled at concentration levels of 50 parts per million (ppm) over an 8 h period according to the Occupational Safety and Health Administration (OSHA). 23 Key characteristics of all three gases are listed in Table I.…”
mentioning
confidence: 99%